In-situ detection of initial products from lignite pyrolysis over modified Y-type zeolites by pyrolysis photoionization time-of-flight mass spectrometry. (November 2020) - Wei, Baoyong; Jin, Lijun; Zhu, Jialong; Hu, Haoquan
Highlights: Py-PI-TOFMS was used to detect lignite pyrolysis products over Y-type zeolites. The physicochemical properties of Y-type zeolites were enhanced by post-treatments. Modified Y-type zeolites obviously changed the distribution of pyrolysis products. The selectivity and intensities of light aromatics were significantly improved. Abstract: Y-type zeolites with different SiO2 /Al2 O3 ratios were used as catalysts to investigate their catalytic effect on initial products of lignite pyrolysis with a novel in-situ pyrolysis photoionization time-of-flight mass spectrometry (Py-PI-TOFMS). Most evolved compounds were in-situ detected during pyrolysis. The modified Y-type zeolites obviously changed the compositions and temperature-evolved profiles of pyrolysis products. Y-1 and Y-2 zeolites prepared by sequential steaming-acid leaching exhibited better catalytic performance, especially dehydroxylation ability. The generation of benzene, toluene, ethylbenzene, xylene, naphthalene and methylnaphthalene (BTEXNMN) was significantly enhanced through dehydroxylation of phenols and naphthol, aromatization of olefins and cracking of large molecules, which could be attributed to their micro-mesoporous structure and suitable acidity. However, Y-3 zeolite, obtained by successive steaming-acid leaching-alkaline solution treatments, presented poor catalytic activity for cracking of pyrolysis volatiles due to few acid sites. This work is helpful to understand the mechanism of catalytic cracking of initial pyrolysis products on Y-type zeolites.